2021
DOI: 10.1007/s00394-021-02716-8
|View full text |Cite
|
Sign up to set email alerts
|

Fine-grained investigation of the relationship between human nutrition and global DNA methylation patterns

Abstract: Purpose: Nutrition is an important, modifiable, environmental factor affecting human health by modulating epigenetic processes, including DNA methylation (5mC).Numerous studies investigated the association of nutrition with global and genespecific DNA methylation and evidences on animal models highlighted a role in DNA hydroxymethylation (5hmC) regulation. However, a more comprehensive analysis of different layers of nutrition in association with global levels of 5mC and 5hmC is lacking. We investigated the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…So far, some analyses on the link between diet and global DNA methylation patterns [ 7 ], as well as diet and site-specific epigenetic changes [ 3 ], have been performed. In terms of site-specific analysis, the main focus of nutri-epigenomic research has been on epigenome-wide association studies (EWAS) of nutrients involved in human C1 metabolism [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, some analyses on the link between diet and global DNA methylation patterns [ 7 ], as well as diet and site-specific epigenetic changes [ 3 ], have been performed. In terms of site-specific analysis, the main focus of nutri-epigenomic research has been on epigenome-wide association studies (EWAS) of nutrients involved in human C1 metabolism [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the analyzed sub-cohort ( N = 1080 with at least an epigenetic measure available) are summarized elsewhere [ 23 ] and in Table 1 . Compared to the whole Moli-sani cohort, the population under study showed similar sex ratio (48.0% vs 48.1% men) but slightly lower age (mean (SD) age 54.9 (11.5) year vs 55.8 (12.0) years, p < 0.0001), due to the removal of prevalent CVD cases.…”
Section: Resultsmentioning
confidence: 99%
“…The study population was already described in Noro et al [ 23 ] and composed of a randomly selected sub-cohort of 1,160 participants of the Moli-sani study ( N = 24,325; 49.20% men; age ≥ 35 years, recruited between 2005 and 2010) [ 53 , 54 ]. Subjects with incomplete dietary questionnaires or with missing values in the studied variables were excluded from the analysis to a final number of 1080 subjects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations